A Swedish population-based study of the mechanisms of parent–offspring transmission of criminal behavior. Issue 5 (17th September 2014) - Kendler, K. S.; Ohlsson, H.; Morris, N. A.; Sundquist, J.; Sundquist, K.
Abstract : Background: While children of parents with criminal behavior (CB) are at increased risk for CB, we have limited knowledge about the causes of this cross-generational transmission. Method: We examined intergenerational continuity in CB in the Swedish population ascertained from the national conviction registers in three family types: intact ( n = 21 11 074), 'not-lived-with' ( n = 16 53 15 where biological parents never lived with their offspring) and 'step' ( n = 1 24 800 offspring) which reflected, respectively, the effects of genes + rearing, genes only and rearing only. We also examined three criminal conviction subtypes: violent CB (VCB), property CB (PCB) and white-collar CB (WCCB). Results: Combined across mothers and fathers, the hazard ratio (HR) for CB in offspring given parental CB was 1.95 in intact, 1.56 in 'not-lived-with' and 1.28 in stepfamilies. In all three family types, all forms of CB in parents (VCB, PCB and WCCB) significantly predicted risk for all forms of CB in offspring. However, VCB in offspring was most strongly predicted by VCB in parents in intact, not-lived-with and stepfamilies. In intact families only, some specific parent–offspring transmission was also seen for WCCB. Conclusions: Both genetic and environmental factors contribute substantially to parent–offspring resemblance for CB. With respect to criminal subtypes, much of parent–offspring transmission appears to be non-specific. However, specific genetic and environmental risk factors for VCB are transmitted across generations. A limitation of these analyses is that CB was assessed only via official criminal convictions.